Study on the effect of solid particle on water-flooding development in low permeability sandstone reservoir - Wu, J.; Meng, H.; Xu, J.; Xie, Sam; Shi, L. (2014)
The solid particles in the injecting water directly affect injection pressure and the degree of formation damage in low permeability sandstone reservoir. The paper studied the injection of three different sizes of solid particle, whose D 90 (the cumulative particle size distribution of solid particle in the injecting water exceeds 90%) is 1.24, 5.05, 9.91 µm. and we studied three kinds of injectivity water for the degrees of damage on oil phase permeability, and investigate the impact on the recovery. The results show there are problems on injectivity in core of permeability less than 1 mD when particle size, D 90 , is larger than 1 µm. However, when the permeability of core is larger than 1 mD, the problem goes away. As D 90 increases, the degrees of oil permeability damage increases and the water flooding recovery reduces. As the permeability grows, the solid particle of larger particle size plugs the flowing channel in small and medium-sized pores, reducing water-flood sweeping ability. Seen from chart of permeability damage, when the core permeability is greater than 10 mD, the particle size, D 90 , can be 5 µm.